Gen-Z’s Dual-Route Message Processing on Tik Tok Through the Heuristic-Systematic Model - Putri Rahmawati (proceedings.icesy, 2026)
This article examined the role of influencer credibility and information on the Tik Tok platform in shaping purchase intentions. The prevalence of overclaim practices in the skincare industry intensified Gen-Z’s consumers’ demand for credible and reliable information. Previous studies generally examined influencer credibility and information separately, highlighting the importance of analyzing both simultaneously on the Tik Tok platform, particularly through the @dokterdetektif account, which presented skincare reviews based on laboratory test results. This study aimed to investigate how Gen-Z’s processed messages through the heuristic and systematic routes of the Heuristic Systematic Model and their influence on purchase intention. Data were collected from 400 Gen-Z’s followers using purposive sampling and analyzed with multiple linear regression using Statistical Package for the Social Sciences software version 26. The results indicated that both message-processing routes had a significant effect on purchase intention, demonstrating an additive effect in which both routes contributed equally to the formation of trust and decision-making. The study concluded that strengthening both influencer credibility and informational quality on Tik Tok content was essential in influencing audience behavior, particularly among Gen-Z’s consumers.